Socio-economic inequalities in survival of patients with prostate cancer: role of age and Gleason grade at diagnosis. - Kashif Shafique; David S Morrison (PLoS ONE, 2013)
In the United Kingdom, survival of prostate cancer patients has improved since the 1990s. A deprivation gap in survival (better survival for the least deprived compared with the most deprived) has been reported but it is not known if differential distribution of earlier age or lower grade disease at diagnosis might explain such patterns. We therefore investigated the impact of age and Gleason grade at diagnosis on the deprivation gap in survival of prostate cancer patients over time. Incident cases of prostate cancer (ICD-10 C61) from the West of Scotland were extracted from the Scottish Cancer Registry from 1991 to 2007. Socio-economic circumstances were measured using the Scottish Index for Multiple Deprivation 2004 (SIMD). Age and deprivation specific mortality rates were obtained from the General Registrar Office for Scotland (GRO(S)). The survival gradient across the five deprivation categories was estimated with linear regression, weighted by the variance of the relative survival estimate. We examined the data for 15,292 adults diagnosed with prostate cancer between 1991 and 2007. Despite substantial improvements in survival of prostate cancer patients, a deprivation gap persists throughout the three periods of diagnoses. The deprivation gap in five year relative survival widened from -4.76 in 1991-1996 to -10.08 in 2003-2007. On age and grade-specific analyses, a significant deprivation gap in five year survival existed between all age groups except among patients' age ≥75 and both low and high grade disease. On multivariate analyses, deprivation was significantly associated with increased excess risk of death (RER 1.48, 95% CI 1.31-1.68, p-value<0.001) independent of age, Gleason grade and period of diagnosis. The deprivation gap in survival from prostate cancer cannot be wholly explained by socio-economic differentials in early detection of disease. Further research is needed to understand whether differences in comorbidities or treatment explain inequalities in prostate cancer outcomes.